Kausalitas Antara Variabel Makro dan Stunting di Sumatera Barat Periode 2021 -2023 - Resfaliza; Kamarni, Neng; Purwasutrisno (Jurnal Informatika Ekonomi Bisnis, 2024)
This research intends to look at the causal relationship between stunting, unemployment, poverty, income inequality, human development index in West Sumatra for the period 2021 - 2023. The type of data used is secondary data in the form of panel data from the Central Statistics Agency (BPS) and the Indonesian Nutrition Status Survey from 2021 to 2023 mapping of 19 regencies/cities in West Sumatra. The data analysis used is vector auto regression analysis (VAR) and vector error correction model (VECM). In inductive analysis there are several tests, namely Optimum Lag Test, Model Stability Test, Johansen Cointegration Test, Granger Causality Test (Granger Causality), VECM Estimation, Impulse Response Function (IRF) Analysis, Forecast Error Variance Decomposition (FEVD) The results of this study show that there is a significant relationship between the human development index and income inequality. There is a significant relationship between unemployment and poverty and income inequality significant relationship between stunting and HDI, poverty, income inequality and unemployment.